100-GHz DD-OFDM-RoF system over 150-km fiber transmission employing pilot-aided phase noise suppression and bit-loading algorithm - Huang, Hou-Tzu; Liang, Wan-Ling; Lin, Chun-Ting; Wei, Chia-Chien; Chi, Sien (Optics express, 2014)
This study extended the transmission distance of a 100-GHz DD-OFDM-RoF system through the reduction of chromatic dispersion-induced phase noise. The implementation of a pilot-aided phase noise suppression (PPNS) scheme enabled the transmission of distance-insensitive 16.97-Gbps QPSK OFDM over 0~150-km fiber and 2-m air transmission via a DFB laser with linewidth of 1~10-MHz. We applied a bit-loading algorithm in conjunction with PPNS to maximize spectral efficiency, resulting in a 93% improvement in the data rate from 11.53 to 22.27 Gbps at a fiber transmission of 150 km.